Antiplatelet resistance in stroke. (February 2011) - Topççuoglu, Mehmet Akif; Arsava, Ethem Murat; Ay, Hakan
Although the exact prevalence of antiplatelet resistance in ischemic stroke is not known, estimates about the two most widely used antiplatelet agents –– aspirin and clopidogrel –– suggest that the resistance rate is high, irrespective of the definition used and parameters measured. Inadequate antiplatelet responsiveness correlates with an increased risk of recurrent ischemic vascular events in patients with stroke and acute coronary syndrome. It is not currently known whether tailoring antiplatelet therapy based on platelet function test results translates into a more effective strategy to prevent secondary vascular events after stroke. Large-scale clinical trials using a universally accepted definition and standardized measurement techniques for antiplatelet resistance are needed to demonstrate whether a ''platelet-function test-guided antiplatelet treatment'' strategy translates into improved stroke care. This article gives an overview of the clinical importance of laboratory antiplatelet resistance, describes the challenges for platelet-function test-guided antiplatelet treatment and discusses practical issues about the management of patients with aspirin and/or clopidogrel resistance.